Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fcvm.2021.717257
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Waist Circumference and the Prevalence of (Pre) Hypertension Among 27,894 US Adults

Abstract: Aims: This study aimed to investigate the association between waist circumference and the prevalence of (pre) hypertension.Methods: Cross-sectional data from the 2007–2018 National Health and Nutrition Examination Survey were analyzed. The historical trend of abdominal obesity was assessed by the Cochran–Armitage trend test. After preprocessed by the multiple imputation strategy, we used generalized additive models to assess the association of waist circumference with systolic/diastolic blood pressure and perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 56 publications
6
19
0
1
Order By: Relevance
“…Interestingly, despite the consistent trend, no statistically significant association was observed in the subgroup of BMI > 28 kg/m 2 . Together with our previous results, 14 , 15 this study supported measuring and managing waist circumference regardless of BMI, which could provide additional opportunities to prevent obesity‐related cardiovascular events.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Interestingly, despite the consistent trend, no statistically significant association was observed in the subgroup of BMI > 28 kg/m 2 . Together with our previous results, 14 , 15 this study supported measuring and managing waist circumference regardless of BMI, which could provide additional opportunities to prevent obesity‐related cardiovascular events.…”
Section: Discussionsupporting
confidence: 83%
“…Our recent cross‐sectional studies demonstrated that high waist circumference could elevate the prevalence of hypertension based on nationally representative US samples from the National Health and Nutrition Examination Survey. 14 , 15 In the US individuals, waist circumference was significantly associated with (pre) hypertension with adjusted odds ratios (95% CI) of 1.28 (1.18–1.40) in the young group and 1.23 (1.15–1.33) in the old group. However, the inherent nature of cross‐sectional design made it difficult to determine the causality between high waist circumference and the development of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…According to the medical literature, males present a distribution of fat in visceral areas, which is strongly associated with metabolic abnormalities as opposed to the fat accumulated at the subcutaneous level observed in females [51,52]. Thus, abdominal obesity is an important risk factor for developing prehypertension in both sexes and is consistent with the results of several epidemiological studies [53][54][55][56]. Therefore, lifestyle changes and pharmacological treatments are appropriate strategies to reduce the risk of obesity in individuals and, consequently, the risk of chronic diseases such as prehypertension, hypertension, and other chronic diseases [57].…”
Section: Discussionsupporting
confidence: 75%
“…Therefore, BMI-defined obesity is insufficient to fully capture the obesity-related metabolic risk. Previous studies have demonstrated that waist circumference is closely associated with multiple cardiovascular diseases and all-cause mortality independent of BMI ( 27 , 41 ). When evaluating obesity-related metabolic risk, these data supported that waist circumference and BMI were irreplaceable adiposity indexes.…”
Section: Discussionmentioning
confidence: 99%